2012
DOI: 10.1038/npre.2012.7136.1
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the mitochondrial genetic code: Towards a unified mathematical framework for the management of genetic information

Abstract: Summary:The origin of the genetic code represents one of the most challenging problems in molecular evolution. The genetic code is an important universal feature of extant organisms and indicates a common ancestry of different forms of life on earth. Known variants of the genetic code can be mainly divided in mitochondrial and nuclear classes. Here we provide a new insight on the origin of the mitochondrial genetic code: we found that its degeneracy distribution can be explained by using a mathematical approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Moreover, the energy interaction argument presupposes an origin of genetic coding in the form of a triplet in which only the first two bases are read. Our recent results point to a radically new hypothesis (not necessarily in contrast with former theories) about the origin of protein coding: the degeneracy of the genetic code arises from key symmetry properties of codons in a nontriplet assignment [35]. In such schemes, the degeneracy assumes a clear physical meaning-that is, the existence of different states of a system with the same energy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, the energy interaction argument presupposes an origin of genetic coding in the form of a triplet in which only the first two bases are read. Our recent results point to a radically new hypothesis (not necessarily in contrast with former theories) about the origin of protein coding: the degeneracy of the genetic code arises from key symmetry properties of codons in a nontriplet assignment [35]. In such schemes, the degeneracy assumes a clear physical meaning-that is, the existence of different states of a system with the same energy.…”
Section: Discussionmentioning
confidence: 94%
“…However, the genetic code has some variants, which can be a product of successive evolution. In any case, it is surprising that the mathematical model based on non-univocal representations of numbers is able to encompass almost all these variants in a unified framework [35]. This fact points to an origin of genetic coding of proteins based on strong organizational principles.…”
Section: Discussionmentioning
confidence: 99%
“…This nice property alert us on the important role of inversion symmetries along coding sequences. In fact, in Gonzalez et al (2012) it has been shown that the symmetries of complementarity and inversion can be used to derive a complete version of a hypothetical primeval mitochondrial code composed of codons of four letters (tesserae). We conclude the section with a corollary and a remark:…”
Section: Structure Of a Circular Codementioning
confidence: 99%
“…This genetic information could in part be related to traces of ancestral codes (El Soufi and Michel, 2017). Indeed, in recent years, various authors have formulated hypotheses about the origin of the modern genetic code in which it is assumed that single amino acids were first encoded by dinucleotides or tetranucleotides, and then later by trinucleotides (see, among others, Baranov et al, 2009;Gonzalez et al, 2012;Patel, 2005; Seligmann, 2014; Wilhelm and Nikolaeva, 2004;Wu et al, 2005). This coding process could have been necessary because the number of amino acids to be encoded increased during the evolution while at the same time nature needed robustness against mutations and translational errors.…”
Section: {A N D Q E G I L F T Y V }mentioning
confidence: 99%